On Almost Semiprime Submodules. (10th September 2014) - Farzalipour, Farkhonde
Abstract : We introduce the concept of almost semiprime submodules of unitary modules over a commutative ring with nonzero identity. We investigate some basic properties of almost semiprime and weakly semiprime submodules and give some characterizations of them, especially for (finitely generated faithful) multiplication modules.